La mémoire des images dans L’Éducation sentimentale - Takashi Kinouchi (Flaubert: Revue Critique et Génétique)
This article studies the references and allusions to images of the 1840s in L’Éducation sentimentale. In this novel Flaubert, explicitly or implicitly, refers to images that characterize those years : Honoré Daumier and Paul Gavarni’s caricatures, Napoleonic etchings, the images of the year 1848, etc. In this article we will explore the memory of these images in L’Éducation sentimentale, shedding new light on the status of the image in Flaubert.